1990
DOI: 10.1002/pd.1970100110
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral congenital short femur: A case report

Abstract: A case of congenital short femur in an otherwise healthy infant is described. Antenatal sonographic diagnosis was made at 26 weeks of gestation. The left femur was shorter than the right (ratio 0.82-0.85). In this case, the occurrence of congenital short femur was sporadic. The diagnosis was confirmed after delivery. This case illustrates the importance of ultrasound as an early detector of certain congenital anomalies and as a useful tool in their follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…Most cases of PFFD are sporadic. Although some have reported a history of exposure to environmental factors such as drugs, viral infections, radiation, and focal ischemia, as well as trauma between the fourth and eighth week of gestation, 1 , 4 others found no evidence of a specific environmental cause, 5 as in our case, and there is still controversy over the etiology. Familial recurrence is quite unusual and chromosomal studies have failed to show any abnormality, but a postulated somatic mutation in the early embryo has been suggested.…”
Section: Discussioncontrasting
confidence: 63%
“…Most cases of PFFD are sporadic. Although some have reported a history of exposure to environmental factors such as drugs, viral infections, radiation, and focal ischemia, as well as trauma between the fourth and eighth week of gestation, 1 , 4 others found no evidence of a specific environmental cause, 5 as in our case, and there is still controversy over the etiology. Familial recurrence is quite unusual and chromosomal studies have failed to show any abnormality, but a postulated somatic mutation in the early embryo has been suggested.…”
Section: Discussioncontrasting
confidence: 63%
“…However, the diagnosis of femoral hypoplasia at an early stage of gestation is less feasible. If the shorter femur has a 50% reduction in a consistent manner with respect to the normal femur length, then at 15 weeks this would represent no more than a difference of about 2 mm from the normal femur and this could well be within the normal range for femoral lengths at that gestation [4]. Nevertheless, Bronstein and Deutsch [5] (1992) discovered a case at 14 WG with transvaginal ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The unilateral form is more common occurring in 85-90% of cases [2]. It has been suggested that PFFD is part of a developmental field defect including FFU syndrome, fibula aplasia-hypoplasia and FH/UFS, since there is a frequent overlap of clinical manifestations among these conditions [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, several ultrasonographic techniques have been reported for the diagnosis of the disease [3,18,19]. In view of the differential diagnosis of the lethal skeletal abnormalities (e.g.…”
mentioning
confidence: 99%